Investigating the relationship between human capital and organizational performance: Insights from the construction industry in Malaysia - Po, Hui Yee; Ting, Irene Wei Kiong; Azim Azuan, Osman; Tan, Shi Yan; Asif, Jawad (Penerbit Universiti Malaysia Pahang, 2024)
The construction industry in Malaysia serves as a cornerstone of economic development, contributing significantly to wealth generation and the creation of vital infrastructure. This study aims to explore the influence of human capital on organizational performance within the Malaysian construction sector. Data was gathered through survey questionnaires distributed to 121 individuals employed in construction firms. Employing a simple random sampling technique, the study utilized partial least squares structural equation modeling for data analysis. The findings of this research reveal compelling insights into the relationship between human capital and organizational performance in the Malaysian construction industry. Specifically, soft skills and educational advancement were found to have a positive and significant impact on organizational performance. However, contrary to expectations, hard skills exhibited a negative effect on organizational performance. In conclusion, the study delves into the theoretical significance, practical ramifications, and future directions.